Quality of life in individuals diagnosed with larynx tumor - Vechi, Geovana Ramazzini; Constantini, Ana Carolina; Chone, Carlos Takahiro; Rossi, Vaneli Colombo (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Introduction: Malignant neoplasm of the larynx (C32), has clinical-stage depending on the tumor (T) and the region of involvement of the larynx. If the patient is assisted by the speech therapist since the pre-surgery up to the rehabilitation helps re-establishing speech communication. Evaluating the quality of life of those individuals makes it possible to understand how the chosen method of the speech rehabilitation interferes with the aspects of the life of those individuals. Objective: Analysing global and voice-related quality of life in individuals diagnosed with a laryngeal tumor. Methodology: 35 participants were invited (29 men and 6 women), all of whom were exclusively diagnosed with T3 and T4 larynx tumors. Characterization data of the sample related to the speech-language intervention were collected. In addition, the respondents answered two specific questionnaires to the quality of life: SF-36 and EORTC QLQ-C30, as well as a specific questionnaire of vocal disadvantage, was applied Voice Handicap Index. Conclusion: Results indicate that although individuals perceive little voice disadvantage, even in adverse communication conditions, the overall quality of life is greatly affected.